Regulation of phosphatidylinositol kinase activity in Saccharomyces cerevisiae. - Holland, K M (1988)
The effects of growth phase and carbon source on membrane-associated phosphatidylinositol kinase in cell extracts of Saccharomyces cerevisiae were examined. Phosphatidylinositol kinase activity increased 2- and 2.5-fold in glucose- and glycerol-grown cells, respectively, in the stationary phase as compared with the exponential phase of growth. The increase in phosphatidylinositol kinase activity in the stationary phase of growth correlated with an increase in the relative amounts of phosphatidylinositol 4-phosphate, the product of the reaction. The increase in phosphatidylinositol kinase activity was not due to the presence of water-soluble effector molecules in cell extracts as indicated by mixing experiments. Phosphatidylinositol kinase activity decreased in cell extracts of exponential-phase cells preincubated under phosphorylation conditions which favor cyclic AMP-dependent protein kinase activity. Phosphatidylinositol kinase activity was not affected in cell extracts of stationary-phase cells preincubated under phosphorylation conditions.